Alternativas orgánicas para el control de moniliasis moniliophthora roreri cif y par en el cultivo de cacao - González Lopez, Galo Cesar (2018)
In all areas where cocoa is grown, including Ecuador, one of the main diseases that affects the production of this crop is Moniliasis caused by the fungus Moniliophthora roreri (Cip and Par), whose damage in production ranges from 20% to 80% and can reach 100%, directly affecting the fruits of all ages, this has caused the genetic erosion of Theobroma cacao L., cacao subspecies that encloses the Criollo cacao and the native complex of Ecuador known as National, displacing the cocoas hybrids such as CCN-51 that is resistant to diseases and has an excellent production, low aroma and flavor, which has led to criticism from some industrial sectors. Currently, chemical controls are the main control route; therefore the present research seeks new organic control alternatives that are economical and friendly with nature, easily accessible to small producers. The main objective was to evaluate the effect of organic alternatives in the control of M. roreri, in cacao type National x Trinitario in the bank of germplasm of cacao of the Farm Santa Inés. Currently the control of the fungus is done by chemical fungicides that contaminate the soil, water, pollinating insects and man when applied and are very expensive. The ash was obtained from the burning of rice husk in the oven of the cocoa germplasm garden and then sieved to remove any impurities that may exist, and then applied to the treatments. Six cocoa plants were selected with the same level of production, the total number of fruits, healthy and a diseased fruit was counted every 15 days for 4 months. Five treatments were evaluated: (T1) Control, (T2) Powdered ash, (T3) Ash diluted in water, (T4) Fossil Shell Agro, (T5) Triomax. The design was completely random with six repetitions. For the statistical analysis, the SPSS program was used. The results of incidence of moniliasis (T2) Ash dust, (T3) Ash diluted in water, (T4) Fossil Shell Agro, (T5) Triomax, do not differ significantly from each other, except the (T1) Control, you can use any of the four treatments mentioned above, opting for any of the three of organic origin (T2, T3, T4) which have a large amount of Si, an element that forms a protective barrier against fungi, also have micro and macronutrients, helping the development of the plants, leaving no waste. According to the economic analysis it could be determined that T3, T2 and T4 are the cheapest and least polluting treatments, providing those that obtained the best benefit per quintal, the (T5) Triomax (chemical fungicide) does not differ significantly from organic treatments , but its high cost and residuality makes it the least profitable option in cocoa production. The (T1) Witness confirms that if the necessary phytosanitary controls are not applied, production may be affected up to 74% in the study area.